ANALISIS TINGKAT KEPUASAN PELANGGAN DALAM PENERAPAN SISTEM BOARDING PASS DI GATE KEBERANGKATAN TERMINAL TERPADU PULO GEBAN - Delvia Yuliana; SITI SAHARA (Universitas Negeri Jakarta, 2021)
The Pulo Gebang Integrated Terminal is the first type A passenger terminal in Indonesia to implement a boarding pass system. The boarding pass system in December 2019- January 2020 is in the trial phase, but in February-March 2020 this system has been implemented 100%. The purpose of this study is to determine whether the passengers are satisfied in using the boarding pass system at the Departure Gate of the Pulo Gebang Integrated Terminal. The research method was carried out by distributing questionnaires to passengers at the Pulo Gebang Integrated Terminal and conducting a few mini interviews with the passengers. This type of research used in this research is quantitative research. In distributing the questionnaire, a purposive sampling. The results of the study were the level of satisfaction with the officers was 82.6%, the level of satisfaction with the terminal facilities was 82.4%, the level of satisfaction with the accessibility was 84.3%, the level of satisfaction with security and comfort was 96%, and the level of satisfaction with the tariffs by 81.8%.